Pd-Phosphinesulfonate bravely battles the ``vinyl halide insertion copolymerization'' barricade - Gaikwad, Shahaji R.; Deshmukh, Satej S.; Chikkali, Samir H. (Journal of Polymer Science Part A-Polymer Chemistry, 2014)
This overview provides insights into the current state-of-the-art solutions to insertion copolymerization of functional olefinic monomers. The challenges in insertion copolymerization of functional olefinic monomers, with a special emphasis on vinyl halides, are highlighted. The crucial design of the Pd-phosphinesulfonate [Pd(PO)] enables up to 3.6 mol % incorporation of vinyl fluoride (VF) in an ethylene-VF copolymerization reaction. In a significant development, insertion copolymerization of industrially relevant functional olefin, that is, vinyl chloride (VC), was unambiguously ascertained, and a detectable amount of VC (0.4 mol %) was incorporated (at the chain end). In a detailed investigation, the in situ existence of (PO)PdH species during the polymerization was revealed, and it was demonstrated that these are indeed responsible for VC incorporation. (c) 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 1-6
Keywords: functional olefin; insertion copolymerization; palladium catalyst; phosphinesulfonate; vinyl chloride